Krüppel like factor 7 regulates mitochondrial dynamics balance in myocardial infarction - Cao Wang; Fuxing Zhu; Lan Zhou; Situo Zhang; Ruiqi Wang; Hui Tian; Bosong Zhang; Jiahui Wu; Xiang Xu; Ruixian Jiang; Xiaolu Hou; Jian Liu; et al. (Communications Biology)
Abstract Targeting the balance of mitochondrial fission and fusion can effectively alleviate the cardiac energy supply efficiency, to restore cardiac systolic dysfunction and reduce mortality. We previously found that Klf7 is closely related to cardiac energy metabolism. Here we generated cardiomyocyte-specific Klf7 knockout and overexpression mice that underwent myocardial infarction (MI) surgery. Klf7 expression increased in the ischemic myocardium of mice, and cardiomyocyte-specific knockout Klf7 significantly lowered the mortality of MI-inflicted mice and improved ATP insufficiency in MI. Subsequently, Klf7 overexpression aggravated adverse cardiac remodeling and mitochondrial fission and fusion imbalance after MI. Our results also demonstrated that Klf7 inhibited mitochondrial fusion and promoted mitochondrial fission by targeting prohibitin 2 (Phb2) and mitofusin 2 (Mfn2). Our study revealed a crucial role in upholding the overall balance of mitochondrial fission and fusion during MI. Furthermore, our findings indicated that the Klf7/Mfn2/Phb2 axis holds promise as a potential target for therapeutic interventions of MI.